KRETERIA REDESAIN PASAR GROSIR DAYA BERBASIS RESPON DAN KEBUTUHAN MASYARAKAT - Mulia, Muhammad Ilham; Mubin, Fathan; Mutmainnah, Mutmainnah (Nature : National Academic Journal of Architecture, 2014)
Two year after the daya Wholesale Market habitation coustructed as from of reponse to market conditions traditionally imaged as a seedy place, dirty, muddy, poorly maintained, and has a very low accupancy level of cuality does not cause society to attract shopping in Daya WholesaleMarket. The this problem, we try to conduct research related to the tendency of the factors that keep people shopping at traditional market, trough this research, authours will try to offer the design criteria based on market data obtained from the results of research thourgh independent and dependent variables on the dependent variables is costumer satisfaction (society) Daya wholesale Market concept disegn that less thant the maximum, causing the need for the rehabilitation market. As result, after two years rehabilitation Daya wholesale Market is not run optimally during the rehabilitation process. So that, Daya Wholesale Market is not preffered by many visitoris, both costumers and producers.